Size controlled synthesis of compact plasmonic blackbodies and a comparative study of wavelengthdependent photothermal therapy - Oh, Wei Jian (2018)
This report provides an overview on metal nanoparticles exhibit interesting plasmonic properties, which can be controlled by their sizes and shapes. Metal nanostructures have been widely used for biosensors because their surface plasmon resonance is extremely sensitive especially towards the local environments and interparticle distance. With the final aim of this project towards new plasmonic biosensors and to develop a class of blackbody materials, this project starts with optimizing the synthesis of Au plasmonic blackbodies. Other steps of biosensor development are involved with surface modification, bioconjugation and spectroscopic detection using UV-vis spectrometer and microscope.